Record pictures photographs from the archives of the Institution of Civil Engineers - Collins, Michael, 1961 January 8- (Thomas Telford, 2004)
Before the invention of photography, civil engineers employed topographic artists to record the progression of their projects. Termed 'record pictures', these are the unacknowledged foundation of the history of photography. This book contains previously unpublished examples.